2015
DOI: 10.1016/j.jcrysgro.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Lateral overgrowth of germanium for monolithic integration of germanium-on-insulator on silicon

Abstract: a b s t r a c tA technique to locally grow germanium-on-insulator (GOI) structure on silicon (Si) platform is studied. On (001) Si wafer, silicon dioxide (SiO 2 ) is thermally grown and patterned to define growth window for germanium (Ge). Crystalline Ge is grown via selective hetero-epitaxy, using SiO 2 as growth mask. Lateral overgrowth of Ge crystal covers SiO 2 surface and neighboring Ge crystals coalesce with each other. Therefore, single crystalline Ge sitting on insulator for GOI applications is achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This process can result in a high crystal quality epilayer although elongated, hemicylindrical voids 7 12 may remain at locations where the growth fronts meet. This phenomenon is attributed to the shape of the growth front at coalescence 7 10 and may be useful in trapping dislocations 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This process can result in a high crystal quality epilayer although elongated, hemicylindrical voids 7 12 may remain at locations where the growth fronts meet. This phenomenon is attributed to the shape of the growth front at coalescence 7 10 and may be useful in trapping dislocations 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Aspect ratio trapping, which is a technique for trapping threading dislocations in a limited Si region at SiO 2 trenches, has been expected to improve the crystallinity of Ge epitaxial films on a Si substrate. [13][14][15] In these reports, the selective growth of a Ge epitaxial layer has been demonstrated by chemical vapor deposition (CVD) with GeH 4 as a Ge precursor. [15][16][17][18] The CVD method is suitable for the selective epitaxial growth because the crystal growth by CVD is strongly dependent on the chemical state of the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In these reports, the selective growth of a Ge epitaxial layer has been demonstrated by chemical vapor deposition (CVD) with GeH 4 as a Ge precursor. [15][16][17][18] The CVD method is suitable for the selective epitaxial growth because the crystal growth by CVD is strongly dependent on the chemical state of the substrate surface. Previously, it was reported that the direct epitaxial growth of the Ge 1−x Sn x layer on a Si substrate was achieved by CVD with hydrogen and chlorine compound precursors such as GeH 4 , Ge 2 H 6 , SnD 4 , and SnCl 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the nanoscale nature of the SAG also helps in lowering the density of the defects formed during the integration of lattice mismatched materials . Threading dislocations formed at the interface of the heterostructure are blocked by the walls of the mask defining the nanoscale openings, leaving the upper part of the NW free of defects (aspect ratio trapping). Most previous SAG studies have focused on the growth of high-quality III–V nanowires and their networks. ,, While there is some work on epitaxial lateral overgrowth of Ge thin films, to the best of our knowledge there is no report on the SAG of in-plane germanium nanowires and networks on Si.…”
mentioning
confidence: 99%